The cacicazgo of the guaranga of mitimaes yungas of Huamachuco (Peru) and the struggle for power between two ethnic authorities during the 17th century - Delgado Dominguez, Carolina (2023)
This paper is a study of indigenous socio-political practices in the former Huamachuco province through the analysis of a legal document from the first decade of the 17th century. We analyze a litigation regarding indigenous political organization that sheds light on interactions between a chiefdom in the highlands and one located in Simbal, in the middle zone between the coast and the highlands. Based on this case study, and on the analysis of the arguments presented by the parties involved, this paper documents the stability of pre-Hispanic practices, even pre-Inca, during the early Colonial period, therein contributing to our understanding history of the region.